2015
DOI: 10.15386/cjmed-441
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Hypertension in Type 2 Diabetes: Prevalence and Patient Characteristics

Abstract: Background and aimsResistant hypertension is defined as failure to achieve blood pressure lower than 140/90 mmHg when using three antihypertensive agents or controlled blood pressure with four or more drugs. We aimed at assessing the prevalence of resistant hypertension and to describe a type 2 diabetes population with resistant hypertension.MethodsThe retrospective observational study included (n=73) type 2 diabetes subjects with resistant hypertension selected from (n=728) subjects admitted to the Centre of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(38 reference statements)
2
3
1
Order By: Relevance
“…Prevalence of RH among diabetic patients was reported by a few studies; RIACE study reported that RH among type 2 diabetic patients was 17% in Spain [16]. Also 10% was the prevalence of RH among Italian type 2 diabetes patients [17]. The result of this study was consistent with other studies conducted among diabetic patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Prevalence of RH among diabetic patients was reported by a few studies; RIACE study reported that RH among type 2 diabetic patients was 17% in Spain [16]. Also 10% was the prevalence of RH among Italian type 2 diabetes patients [17]. The result of this study was consistent with other studies conducted among diabetic patients.…”
Section: Discussionsupporting
confidence: 90%
“…Previous epidemiologic studies indicated that the prevalence of RH among hypertensive population ranges from 10% to 30% [10]. Many studies reported that diabetes was a significant risk factor of RH occurrence among hypertensive patients [10,[12][13][14][15][16][17][18][19][20][21]. In comparing the results of this study with others which were conducted among hypertensive patients without type 2 diabetes, the prevalence of RH was higher.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This is because it was a community-based study; i.e., there is a difference in the study population. The lowest findings were in the Netherlands with prevalence of 15% [15] and in the study done in Romania with prevalence of 10% [16]; this is because of the different methodology used in our study, they used cohort, and the retrospective nature of the study, respectively.…”
Section: Discussioncontrasting
confidence: 58%
“…The prevalence of resistant hypertension with type 2 diabetes mellitus (T2DM) varies in different countries. A study published in 2015 estimated that the prevalence of resistant hypertension was 10% in Romania [5]. Moreover, according to the National Health and Nutrition Examination Survey (NHANES), the prevalence of resistant hypertension was 8.9% in the United States between 2003 and 2008, and has increased to 13% in…”
Section: Introductionmentioning
confidence: 99%